Exotics in the Wetlands: West Indian Marsh Grass - Rodrigo Diaz; William A. Overholt; James P. Cuda (EDIS)
Exotic plant species in Florida wetlands spread rapidly due to floods, large waterway systems, and extensive traffic of commercial and recreational boats. Fertilizer and sediment runoff from agricultural lands and waste water from beef and dairy operations may contribute to successful establishment of exotic aquatic plants. West Indian Marsh Grass, Hymenachne amplexicaulis (Rudge) Nees (Poaceae), is one of many species currently invading sensitive wetlands in central and south Florida. This document is ENY-693, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: December 2003.